Physical Exercise Prevented Stress‐Induced Anxiety via Improving Brain RNA Methylation. Issue 24 (1st June 2022) - Yan, Lan; Wei, Ji‐an; Yang, Fengzhen; Wang, Mei; Wang, Siqi; Cheng, Tong; Liu, Xuanjun; Jia, Yanbin; So, Kwok‐Fai; Zhang, Li
Abstract: Physical exercise is effective in alleviating mental disorders by improving synaptic transmission; however, the link between body endurance training and neural adaptation has not yet been completely resolved. In this study, the authors investigated the role of RNA N 6 ‐methyladenosine (m6A), an emerging epigenetic mechanism, in improved resilience against chronic restraint stress. A combination of molecular, behavioral, and in vivo recording data demonstrates exercise‐mediated restoration of m6A in the mouse medial prefrontal cortex, whose activity is potentiated to exert anxiolytic effects. Furthermore, it is revealed that hepatic biosynthesis of one methyl donor is necessary for exercise to improve brain RNA m6A to counteract environmental stress. This novel liver‐brain axis provides an explanation for brain network changes upon exercise training and provides new insights into the diagnosis and treatment of anxiety disorders. Abstract : N 6 ‐methyladenosine (m6A) is one common posttranscriptional modification of mRNA molecules and is related with neural functions. Aerobic exercise can elevate the hepatic synthesis of methyl donor molecules, which potentiate the m6A of synaptic transcripts in medial prefrontal cortex to counteract stress‐induced anxiety. The current findings uncover a liver‐brain axis under exercise paradigms to mediate central epigenetics and mental functions.